O olhar e o corpo na relação transferencial com uma criança em sofrimento psíquico grave - Januário, Lívia Milhomem; Tafuri, Maria Izabel (Estilos da Clinica, 2008)
This article is focused on the transference in the psychoanalytic clinic with children in serious psychic suffering. The reflection is on the importance of thinking the transferencial relation far beyond the interpretation and the importance of the non-verbal sensorial bonds in the transference handling. Using Winnicott as a theoretical and clinical reference, an evolution of the analysis of a child who had established a holding set is related, where the transference was marked by the look and the body of the annalist, making possible the resumption of the child psychic constitution process.